Potential risk of Bacillus cereus in spices in Turkey. (February 2022) - Cufaoglu, Gizem; Ayaz, Naim Deniz
Abstract: Spices are widely used all over the world in food preparation to give taste, smell and color as well as to preserve food products. Bacillus cereus is a common contaminant in spices which can cause food poisoning due to its toxins. This study focused on determining the presence of B. cereus as well as the toxin profiles of the strains. A total of 203 packaged and unpackaged spice samples were collected during the study. B. cereus prevalence was determined as 31.5%. Also, B. thuringiensis was identified in five samples (2.5%). The prevalence of B. cereus in non-irradiated spices (41.5%) was found significantly higher than the irradiated ones (20.7%) (p < 0.05). Moreover, the isolates were examined for nine toxin genes, and entFM (94%) was found as the most abundant gene, followed by cytK (60%) and hblD (60%) genes. No cesB gene was found in isolates. Among the strains only a B. thurgiensis isolate was found to have eight toxin genes. The results show that B. cereus is a potential public health risk in spices. Considering the possibility of contamination of foods by B. cereus via spices, effective decontamination methods should be applied and precautions should be taken to control growing of B. cereus and forming toxins during food preparation and pre-serving stages. Highlights: Prevalence of B. cereus in spices was 31.5%. B. thuringiensis was identified in 5 of 203 (2.5%) spice samples. EntFM (94%), cytK (60%) and hblD (60%) were the most abundant toxin genes. No cesB gene was found in isolates (0/89). The contamination in non-irradiated spices was significantly higher (p < 0.05).